1990
DOI: 10.1055/s-2007-1024860
|View full text |Cite
|
Sign up to set email alerts
|

Medical Implications of the Lactate and Ammonia Relationship in Anaerobic Exercise*

Abstract: The genesis of the modern ischemic forearm exercise test (IFET) employing the measurement of lactate and ammonia as countervailing metabolites is briefly reviewed, along with the application of the lactate ammonia exercise ratio in the diagnosis of myoadenylate deaminase deficiency and disorders of glycolysis and glycogenolysis. Two cases are presented to illustrate the response patterns elicited, their reproducibility, the types of parameters that can be quantified, and the role the IFET may play in the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…It has to be noted that, in contrast with the voluntary exercise protocols used thus far [4,8,14,15], only a small muscle was activated in the present study. The adductor pollicis muscle was chosen for practical reasons : it can easily be maximally activated by electrical stimulation of the nerve, and its force can be measured without interference of other muscles.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…It has to be noted that, in contrast with the voluntary exercise protocols used thus far [4,8,14,15], only a small muscle was activated in the present study. The adductor pollicis muscle was chosen for practical reasons : it can easily be maximally activated by electrical stimulation of the nerve, and its force can be measured without interference of other muscles.…”
Section: Discussioncontrasting
confidence: 50%
“…The main conclusion of the present work is that there were no significant differences in adductor pollicis muscle power output between the MAD-deficient and the control subjects before, during or after short-term maximal dynamic exercise. Some previous studies showed an effect of MAD deficiency on performance during exercise of rather moderate intensity [4,8,15], whereas others failed to show such an effect during more intensive exercise [14,16]. There are indications that MAD deficiency is a harmless polymorphism and not a disease in itself [11,23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Methods: Twenty-six healthy subjects and 32 patients with exercise intolerance performed an isometric exercise at 70% of the maximal voluntary contraction during 30 seconds in non-ischemic conditions. 3,4,[11][12][13] The main variable methodologic factors are the intensity and duration of exercise, the contraction type, the assessment of the muscle work, the subjective sensation of fatigue and pain during the exercise, and the protocol of blood sampling. Results: A nearly fourfold lactate rise was induced by exercise in healthy subjects.…”
mentioning
confidence: 99%
“…The ischemic forearm exercise test allows also a presumptive diagnosis of MADD when a negligible increase in blood ammonia despite a normal rise in lactate occurs [50][51][52].…”
Section: Ischemic Forearm Exercise Testmentioning
confidence: 99%